Identification of Dust Storm Sources in Iraq using Space Monitoring Tools - Mohammed, Abdulkareem; Alomari, Maath (Iraqi Journal of Science, 2024)
The earth cover (soil types) of Iraq is characterized by its variation in its geological and mineral contents. A large area of Iraq can be a source for dust storms that occur in Iraq and neighboring countries. These areas are located in the north western and western parts of Iraq which are characterized by their dryness and minimum vegetation during summer season. The prevailing wind direction in Iraq comes from the northwest and is known as ( Shamal). This cold wind front meets a warm air front from the west on areas of soft and light soil cover in north western part of Iraq. This process leads to rise of huge amount of suspended dust and hence to the creation of dust storm which propagate in most parts of Iraq (middle and south).In this research we observe the occurrence frequency of dust storms as observed from space images and meteorological data. The source of dust storm is also indicated using these space tools.